Sources of Funds and Quality Effects in Higher Education - William O. Brown Jr. (Claremont McKenna College, Department of Economics, 1999)
Economists have suggested that the quality of higher education is not independent of the sources of funds used to fund that education. This paper examines the relationship between student measures of teaching quality and institutional revenue sources. The results indicate that a greater reliance on private subsides is associated with higher measures of teacher quality. A greater reliance on public subsidies, however, leads to lower teacher quality ratings. The importance of these results for shaping public policy decisions is also discussed.
Keywords: I22; L30; H42; 330; higher education; educational finance